Hydro-geochemical investigations of arsenic rich groundwater using multivariate statistical analysis - N M Refat Nasher; Sharmin Zaman Emon (National Geographical Journal of India, 2023)
Multivariate statistical analysis has been applied to assess the chemical characteristics of high arsenic groundwater from the central-southern part of Bangladesh. A total of 43 shallow groundwater samples were collected and analyzed. The groundwater is almost neutral. The results of cations and anions trends are Na>Ca>Mg>K and HCO3>Cl>SO4>NO3 , respectively. Alkalinity has a significant positive correlation with Mg, Ca and K suggesting silicate weathering as the major process of controlling groundwater geochemistry. The significant positive correlation between Na and Cl indicates the seawater intrusion into groundwater. The R-mode cluster allows variables into four groups. Alkalinity, Mg, K in the first and Ca in the second, Na and Cl in the third cluster indicate silicate weathering and carbonate dissolution and seawater intrusion, respectively. R-mode factor analysis allows variables into four components having eigen values more than 1 which represent 72.5% of total variances. Component 1 positively loaded with K, Mg, P, and alkalinity suggest silicate weathering. Component 2 positively loaded with Na and Cl suggests seawater influences groundwater. Component 3 positively loaded with Ca suggest the carbonate dissolution. The Q-mode cluster analysis represents the highest Fe concentrations